Animal abuse proclivity: behavioral, personality and regulatory factors associated with varying levels of severity - Parfitt, Charlotte Hannah (Psychology, crime & law, 2018)
To date, research into adult-perpetrated animal abuse has consisted of studies using forensic and psychiatric samples. Given that animal abuse goes largely unreported, it is unclear whether the findings from the current literature are generalizable to unapprehended, undetected abusers in the community. However, the emergence of proclivity methodologies fills this gap by examining the relationships between animal abuse propensity and factors such as empathy, attitudes towards animals and antisocial behavior. The current study aimed to extend this literature by examining further individual-level variables (i.e. personality traits) and behavioral factors as correlates of animal abuse proclivity and as a function of varying levels of animal abuse severity (e.g. neglect versus severe violence). One hundred and fifty participants took part in this correlational study. We found low extraversion, agreeableness, neuroticism, anger regulation, and illegal behavior to be significant factors related to animal abuse proclivity. We also found low extraversion, anger regulation, and illegal behavior to be significant factors across varying levels of animal abuse severity, but low neuroticism to be a unique factor related to less severe forms of animal abuse proclivity. These findings are further discussed in light of their theoretical and treatment implications.